Social representations of the Brazilian national health care system in the city of Rio de Janeiro, Brazil, according to the structural approach (Revista Latino-Americana de Enfermagem, 2008)
The Brazilian National Health Care System The Single Health System (SHS) [SUS-Sistema Único de Saúde] faces difficulties for its effective implementation. This paper aims to characterize the contents and the social representation structure of the Brazilian health care system among health care professionals in the city of Rio de Janeiro. The concept of social memory and the theory of social representation were adopted as frameworks. Five health care institutions were included in this research, with 100 professionals altogether. The free-association technique was used to collect data and the EVOC 2003 software was used analyzed for data analysis. The results signal to a central nucleus, characterized by negative attitudes regarding the SUS. In the contrast area, there is a negative attitude towards the effectiveness of the system and a positive attitude towards the care provided to service users, also showing other principles. At its periphery, the implementation of new opinions about the representation could be observed. It is concluded that the professionals present social representations that recognize the SUS as a new system, eliciting negative attitudes among the professionals, and that is in a process of formation or progressive transformation, raising judgments about the pertinence of the system's principles.